Phytoremediation Potentials of Some Nigerian Weeds - EDDY, N.O.; EKOP, A.S. (Asian Journal of Chemistry, 2010)
The potentials of Phyllanthus amarus (chanca piedra), chromolaena odorate (awolowos weed), Stachytarpheta indica (gervao), Bryophyllum pinnatum (life leaf) and Murraya koenigii (curry leaf) to absorbed, Pb, Zn, Cd, Cu and Ni from contaminated soil. The plants were allowed to germinate in a pre-analyzed natural soil (within 2 weeks) after which they were transplanted to contaminated soil. After 5 weeks exposure, the plants were removed and the soil and the plants were analysed for their heavy metals content. The absorption capacity of these plants for Pb, Zn, Cd, Cr, Cu and Ni shows that Stachytarpheta indica, Phyllanthus amarus, Murraya koenigii, Phyllanthus amarus, Phyllanthus amarus, Phyllanthus amarus and Phyllanthus amarus have the potentials of absorbing heavy metals from contaminated soil.